Knowledge of the Female Athlete Triad, and prevalence of triad risk factors among female high school athletes and their coaches - Brown, K. N.; Wengreen, H. J.; Beals, K. A. (Journal of Pediatric and Adolescent Gynecology, 2014)
Study Objective: This study aimed to determine awareness/knowledge of the Triad and its health implications among female high school athletes and their coaches, and to evaluate coaches' Triad screening/intervention practices. Design: Cross-sectional survey. Setting: Two high schools in the western United States. Participants: Female athletes from a variety of sports (N = 240) ages 14-18 years and their coaches (N = 10). Intervention: Participants completed surveys that assessed Triad knowledge and athlete Triad risk factors. Main Outcome Measures: Frequency of responses to Triad knowledge, Triad risk factor, and Triad education/screening procedures questions; athlete summative knowledge score. Results: Half (N = 120) of participants reported menstrual irregularity, and 42% (N = 101) had 2 or more Triad risk factors: past amenorrhea (N = 39), past stress fracture (N = 41), self-reported not eating enough (N = 53), underweight (BMI-for-age < 5th percentile) (N = 10), pressure to be a certain weight (N = 143), and wanting to lose >10 pounds when self-reported weight was in a healthy range (N = 34). Average athlete Triad knowledge score was 2.97 ± 1.61 out of 8. Coach Triad knowledge was limited; however, most (9/10) were comfortable discussing menstruation with their athletes. Barriers to Triad screening/education were coaches' insufficient time, knowledge, and educational resources. Conclusion: Triad risk factors were prevalent among athletes and coach and athlete Triad knowledge was low. Providing coaches with Triad screening/education training may increase Triad knowledge and decrease Triad risk among high school athletes.